2017
DOI: 10.4236/aasoci.2017.78019
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Communication Effect of Augmented Reality Technology in Electronic Publications among Youth—A Case Study of “Augmented Reality Interactive Science Reading”

Abstract: Based on Technology Acceptance Model (TAM), this paper constructs the augmented reality electronic publication communication effect model (AREPCEM) and analyzes the data among youth. It is found that the first-level index (use and recognition) and second-level indicators (external variables, perceived usefulness, perceived ease of use, satisfaction, dependency) have positive relevance to audience recognition among youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Zhu built an augmented reality electronic publication dissemination effect model (ARE-PCEM) based on the technology acceptance model (TAM) and analyzed the data of adolescents. The study found that the primary indicators (use and recognition) and secondary indicators (external variables, perceived usefulness, perceived ease of use, satisfaction, and dependence) are positively correlated with the recognition of teenagers [7]. Science proposed that when the signal between the brain and one eye is wrong, the input from the other eye may dominate.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu built an augmented reality electronic publication dissemination effect model (ARE-PCEM) based on the technology acceptance model (TAM) and analyzed the data of adolescents. The study found that the primary indicators (use and recognition) and secondary indicators (external variables, perceived usefulness, perceived ease of use, satisfaction, and dependence) are positively correlated with the recognition of teenagers [7]. Science proposed that when the signal between the brain and one eye is wrong, the input from the other eye may dominate.…”
Section: Introductionmentioning
confidence: 99%
“…Важливими, на думку авторів Ю. Чу (Yu. Zhu), Г. Йе (H. Ye), С Танг (S. Tang) [27], є індивідуальна та групова робота з використанням різних гаджетів для візуалізації контенту доповненої реальності.…”
Section: проблематика використання технології доповненої реальності в...unclassified
“…In the development of historical and cultural resources, people can experience narrative and story information that has never appeared in reality through augmented reality technology, and have a variety of possible interactions with the environment, so as to obtain a deep sense of pleasure from historical culture. Based on augmented reality, this paper studies its basic ideas and implementation methods in the digital protection of religious tourism resources, and provides reference for the theoretical research and practical application of augmented reality technology in the field of digital protection [4].…”
Section: Introductionmentioning
confidence: 99%